The Influence of YouTube TED Talks Video on Speaking Skills Mastery (A Quasi Experimental Study at one of the Tertiary Schools in Lebak-Banten) - Suryati, Eva; Handayani, Rita; Aisah, Siti (Journal of Linguistics, Literacy, and Pedagogy, 2025)
The purpose of this study was to find out the effect of TED Talks videos on YouTube towards eleventh-grade students' speaking ability at one of the tertiary schools in Lebak, Banten. With the application of quasi-experimental design and non-equivalent control group, quantitative approach was used. The sample population was 46 students who were allocated to two groups of 23 students each: the experimental and the control groups. Speaking proficiency pre- and post-tests were employed as the research tool in this study. Normality, homogeneity, content validity, inter-rater reliability, and hypothesis testing by the procedure of t-test were all employed to examine the data. On a significance level of 0.05 (5%), the computation indicates that the value of ???????????????????????? is higher than ???????????????????????? (5.25 ≥ 2.00). It can be inferred that the TED Talks videos on YouTube influence the speaking abilities of eleventh grade students. English teachers are advised to use YouTube TED Talks videos to assist their pupils become more proficient speakers.